Efektivitas Komunikasi Interpersonal Untuk Meningkatkan Komitmen Organisasi - , Berliana Sari Oktaria, Dr. Magda Bhinnety, M.Si., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Commitment to the organization is an important aspect that should be owned by a member of the organization. This is because of the organization itself, the performance of an organization depends on the commitment of its members. The studies of some, suspected interpersonal communication is an effective way to bridge the problem of the organization. This is because an individual's social needs can be met with the interaction between members of the organization, it will create a favorable climate in an effort to build and enhance members' commitment to the organization. Therefore, this study aims to improve the individual's organizational commitment through interpersonal communication training. Subjects involved in the study were 20 employees of PT Cahaya Fortuna Sejati. Theese 20 subjects were then divided randomly into 2 groups: the experimental group and the control group. Organizational commitment was measured using a scale adapted from the organizational commitment organizational commitment scale developed by Mowday, Porter and Steers (1982). Measurements were taken before and after treatment in both groups were subjected to detect differences in organizational commitment after treatment. The experimental group was treated in the form of interpersonal communication training program for 1 day (8 hours effective) and the untreated control group (included in the waiting list group) for the training of this group will be given after the experimental group was given the post test. The data was analized with Mann-Whitney test. The results showed that the training of interpersonal communication can be effective to improve organizational commitment F = 0,025 (p<0,05).